Clinical and metabolic consequences of L-serine supplementation in hereditary sensory and autonomic neuropathy type 1C - Auranen, Mari (Cold Spring Harb Mol Case Stud, 2017)
Hereditary sensory neuropathy type 1 (HSAN1) may be the first genetic neuropathy amenable to a specific mechanism-based treatment, as L-serine supplementation can be used to lower the neurotoxic levels of 1-deoxysphingolipids (1-deoxySL) that cause the neurodegeneration. The treatment is so far untested in HSAN1C caused by variants in the serine palmitoyl transferase subunit 2 (SPTLC2) gene. The aim of this study was to establish whether oral L-serine lowers 1-deoxySL in a patient with HSAN1C, to perform a dose escalation to find the minimal effective dose, and to assess the safety profile and global metabolic effects of the treatment. Our patient underwent a 52-wk treatment in which the L-serine dose was titrated up to 400 mg/kg/day. She was followed up by repeated clinical examination, nerve conduction testing, and skin biopsies to document effects on small nerve fibers. Serum was assayed for 1-deoxySL and metabolomics analysis of 111 metabolites. We found a robust lowering of 1-deoxySL, which correlated in a near-linear fashion with increased serum L-serine levels. Metabolomics analysis showed a modest elevation in glycine and a marked reduction in the level of cytosine, whereas most of the other assayed metabolites did not change. There were no direct side effects from the treatment, but the patient developed a transitory toe ulceration during the course of the study. The Charcot–Marie–Tooth neuropathy score increased by 1 point. We conclude that oral supplementation of L-serine decreases 1-deoxySL in HSAN1C without major global effects on metabolism. L-serine is therefore a potential treatment for HSAN1C.